The digital art of marbled paper - Akgun, BT (MIT PRESS, 2004)
The author describes his development of a computer-based paper-marbling tool, based on a traditional Turkish art form in which marbled-paper figures and patterns are created on the surface of a liquid bath. Similar works can be obtained by simulating fluid flows on a computer, using the Navier-Stokes equations as the physical model of the fluid flows. The author has created an application program that includes marbling tools. Such a program must run in real time, so that hand-eye coordination is required of the user. Real-time simulation of fluid flows requires much processor power. The author has attempted to adapt this technique for use with a personal computer. To decrease the processing power required, the image size may be decreased, but the results may not be as satisfactory.
Keywords: Art